2018
DOI: 10.3390/ijgi7030103
|View full text |Cite
|
Sign up to set email alerts
|

ENSO- and Rainfall-Sensitive Vegetation Regions in Indonesia as Identified from Multi-Sensor Remote Sensing Data

Abstract: Abstract:Ongoing global warming has triggered extreme climate events of increasing magnitude and frequency. Under this effect, a series of extreme climate events such as drought and increased rainfall during the El Nino Southern Oscillation (ENSO) are expected to be amplified in the coming years. Adequate mapping of regions with climate-sensitive vegetation and its associated time lag is required for appropriate mitigation planning to avoid potential negative ecological impacts towards vegetation. In this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…Several studies [28][29][30] analyzed the covariation of climate indices PDO, NAO, and SOI with precipitation to assess to assess meteorological and hydrological drought in Iran. Also, in other parts of the world, some research were carried out on the relationship between climate indices and hydrological variables [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies [28][29][30] analyzed the covariation of climate indices PDO, NAO, and SOI with precipitation to assess to assess meteorological and hydrological drought in Iran. Also, in other parts of the world, some research were carried out on the relationship between climate indices and hydrological variables [31,32].…”
Section: Introductionmentioning
confidence: 99%
“…CHIRPS data, which has previously been utilised in Indonesia and other regions of the Maritime Continent for analysing rainfall extremes and trends, has been validated by a number of researchers (Arjasakusuma et al 2018;Nugroho et al 2021). In this study, for validation purposes of CHIRPS, daily rainfall data for two observed stations were obtained: Paseh (Lat:-7.057, Lon:107.764) and Kertasari (Lat:-7.192, Lon:107.677) situated in Majalaya (Fig.…”
Section: Rainfall Datamentioning
confidence: 99%
“…The preceding warm events (El Niño) in the cold season over the Niño-3 region usually led to following wetter spring and wetter plum rainfall with frequent extreme events before summer in Taiwan, and vice versa [55,58]. Several studies using remotely sensed data showed that spatiotemporal patterns of the vegetative surface were connected with ENSO indicators which were linked to temperature in mid-latitude [43,116], rainfall variability, and flood in tropical Indonesia and the Amazon [49,50,117,118]. Our results showed that the patterns of the first three PCs were primarily controlled by local climatic factors, whereas the weak but substantial climatic signals associated with ENSO only can be captured by the low variance of vegetation using minor PC loadings (Figures 7-10).…”
Section: Spatiotemporal Patterns Of Vegetation Growth Associated With Land Surface Phenology and Climatic Fluctuationsmentioning
confidence: 99%